The declarations of the parties and the testimonies of the witnesses in cases of marriage annulment ob exclusionem indissolubilitatis - KRAJCZYŃSKI, JAN (Prawo Kanoniczne, 2014)
The author of the paper addresses the issue of importance of the two fundamental means of proof in nullifying marriage trials due to exclusion of indissolubility of the marriage i.e. the declaration of the parties and the testimonies of the witnesses. On the basis of analysis of the latest jurisprudence of the Apostolic Tribunal of the Roman Rota, the author first intends to specify the nature, characteristic features and the evidence value of the means such as judicial admission of the simulant, non-judicial admission of the simulant, declaration of the spouse, and, testimony of the witness. Eventually, the author advocates particular caution and attention while evaluating the quality and importance of such declarations and testimonies.